The impact of recovery time on performance in Division I collegiate beach volleyball players - Holtgeerts, R. N.; Gann, J.; Jung, H. C.; Hey, W. (The Journal of Strength and Conditioning Research, 2022)
The sport of beach volleyball has recently grown significantly at the collegiate level, and collegiate beach volleyball players often practice and compete 5 or 6 days per week during the competitive season. This study examined the effects of the amount of recovery time on performance in Division 1 Collegiate beach volleyball players. Ten female NCAA Division 1 beach volleyball players, aged 20.2 ± 1.23 years, participated in the study. Subjects completed 2 trials consisting of 4 sessions of volleyball play (with a 24-hour recovery trial and 48-hour recovery trial). Trials were randomized and counter balanced. Each trial measured counter-movement jump, 5-10-5 agility time, 3 beach volleyball drills, and scores of a beach volleyball match. Perceived recovery, sleep quality, and rating of perceived exertion were also recorded. The significance level set for the study was p = 0.05. Counter-movement jump showed small but significant increases following the 24-hour recovery period (p = 0.05). 5-10-5 agility test showed significant improvement with the 48-hour recovery period (p = 0.05). Perceived Recovery scores demonstrated significant increases in both recovery periods (p = 0.05). Beach volleyball drill and match performance were not affected by the change in recovery time. These results indicate that, although some physical skills are affected by recovery time, beach volleyball performance as a whole is relatively stable over several days. It is normal for NCAA athletes to play back-to-back days and with little recovery time, and these results indicate that this practice does not negatively affect sport performance.